2009
DOI: 10.1038/aps.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific regulation of the Na+-K+ pump by adenosine in guinea pig ventricular myocytes

Abstract: Aim: The present study investigated the effect of adenosine on Na + -K + pumps in acutely isolated guinea pig (Cavia sp.) ventricular myocytes. Methods: The whole-cell, patch-clamp technique was used to record the Na + -K + pump current (I p ) in acutely isolated guinea pig ventricular myocytes. Results: Adenosine inhibited the high DHO-affinity pump current (I h ) in a concentration-dependent manner, which was blocked by the selective adenosine A 1 receptor antagonist DPCPX and the general protein kinase C (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…4 The A 3– selective agonist Cl-IB-MECA was able to induce protection against hypoxia in a neonatal rat cardiomyocyte model, 35 but there are little available data confirming whether A 3 AR are actually expressed in adult cardiac myocytes. Zhang et al 36 found that A 1 AR-selective agonists inhibited high dihydro-ouabain sensitive Na + -K + current in guinea pig ventricular myocytes, whereas Cl-IB-MECA had no effect causing them to conclude that adult cardiomyocytes do not express A 3 AR, at least in that species. The present results, however, clearly reveal A 3 AR in the sarcolemma of adult rabbit cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4 The A 3– selective agonist Cl-IB-MECA was able to induce protection against hypoxia in a neonatal rat cardiomyocyte model, 35 but there are little available data confirming whether A 3 AR are actually expressed in adult cardiac myocytes. Zhang et al 36 found that A 1 AR-selective agonists inhibited high dihydro-ouabain sensitive Na + -K + current in guinea pig ventricular myocytes, whereas Cl-IB-MECA had no effect causing them to conclude that adult cardiomyocytes do not express A 3 AR, at least in that species. The present results, however, clearly reveal A 3 AR in the sarcolemma of adult rabbit cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 22) Interestingly, some researchers reported that artemisinin has an antiarrhythmic effect by inhibiting multiple ion channels. 9) 10) Yang et al 7) 8) demonstrated that artemisinin significantly inhibited the potassium outward current of I to channels in the Purkinje fibers by 84% at 100 μM in a concentration-dependent and reversible manner. The concentration of artemisinin used (100–150 μM) in the current study was based on that report.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antimalarial effect, its antiarrhythmic effect, which includes suppression of the I K1 , I to , and I Ks channels, was reported previously. 7) 8) 9) 10) Therefore, we evaluated the hypothesis that inhibition of I to channels by artemisinin may play a role in the suppression of ventricular arrhythmia in canine wedge preparation models of BrS.…”
Section: Introductionmentioning
confidence: 99%
“…The postulated mechanisms include 1) These were in the distribution area of the facial nerve, and the volume of bee venom was large. Melittin might inhibit the activity of Na + -K + -ATPase on the nerve synapse through the above mechanism, 12 resulting in facial nerve paralysis. 2) Bee venom is composed of proteins like hyaluronidase, phospholipase, peptides like secapin, apamin, procamine, and active amines like histamine and apamin.…”
Section: Discussionmentioning
confidence: 99%